Find the remainder when 2 4 1 is divided by 2 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
why can't we have 2 as a remainder using Euler's theorem
By Fermat's little theorem , 2 2 2 ( m o d 2 3 ) ≡ 1 ⟹ 2 4 4 ( m o d 2 3 ) ≡ 1 ⟹ 2 4 1 ⋅ 2 3 ( m o d 2 3 ) ≡ 1 ⟹ 2 4 1 ( m o d 2 3 ) ≡ 8 − 1 . We're left to find the multiplicative inverse . That is, we have to find the smallest positive integer x such that there exist an integer y satisfying 8 x + 2 3 y = 1 . A simple trial and error shows that ( x , y ) = ( 3 , − 1 ) . Hence, 2 4 1 ( m o d 2 3 ) ≡ 3 .
I have a question why can't we use Euler's theorem in this case? as phi(41) --> will result in 40 and hence our sum will be easier
Log in to reply
I believed you got your Euler theorem formula messed up. Please read up Euler's totient function again.
Log in to reply
Yeah, I read but could not understand, can you tell me where is the problem?
Log in to reply
@Dibyojyoti Bhattacharjee – ETF states that if a and b are coprime, then a c m o d c = a c m o d ϕ ( b ) m o d b .
In this case, a = 2 , c = 4 1 , b = 2 3 . So you're not computing ETF(41) at all.
Log in to reply
@Pi Han Goh – Thanks for the help, and sorry for troubling you with this little issue...
Log in to reply
@Dibyojyoti Bhattacharjee – Not at all. We come here to learn after all!
Problem Loading...
Note Loading...
Set Loading...
2 4 1 ≡ 2 6 × 6 + 5 (mod 23) ≡ 2 5 ( 6 4 ) 6 (mod 23) ≡ 3 2 ( 6 9 − 5 ) 6 (mod 23) ≡ 9 × 5 6 (mod 23) ≡ 9 × 2 5 3 (mod 23) ≡ 9 × ( 2 3 + 2 ) 3 (mod 23) ≡ 9 × 2 3 (mod 23) ≡ 9 × 8 (mod 23) ≡ 7 2 (mod 23) ≡ 3 (mod 23)